Linked health data for pharmacovigilance in children: perceived legal and ethical issues for stakeholders and data guardians. Issue 2 (12th February 2014) - Hopf, Yvonne Marina; Bond, Christine B; Francis, Jill J; Haughney, John; Helms, Peter J
Abstract : Objective: The inclusion of the Community Health Index in the recording of National Health Service (NHS) contacts in Scotland facilitates national linkage of data such as prescribing and healthcare utilisation. This linkage could be the basis for identification of adverse drug reactions. The aim of this article is to report the views of healthcare professionals on data sharing, ownership and the legal and other applicable frameworks relevant to linkage of routinely collected paediatric healthcare data. Design: Qualitative study using semistructured face-to-face interviews addressing the study aims. Participants: Purposive sample of professional stakeholders (n=25) including experts on ethics, data protection, pharmacovigilance, data linkage, legal issues and prescribing. Interviews were audio-recorded, transcribed and thematically analysed using a framework approach. Results: Participants identified existing data sharing systems in the UK. Access to healthcare data should be approved by the data owners. The definition of data ownership and associated legal responsibilities for linked healthcare data were seen as important factors to ensure accountability for the use of linked data. Yet data owners were seen as facilitators of the proposed data linkage. Twelve frameworks (legal, regulatory and governance) applicable to the linkage of healthcare data were identified. Conclusions: A large number of potentially relevant legal and regulatory frameworks were identified. Ownership of the linked data was seen as an extension of responsibility for, or guardianship of, the source datasets. The consensus emerging from the present study was that clarity is required on the definition of data sharing, data ownership and responsibilities of data owners.